The relationship between parenting style with adolescent identity development in Karangploso district, Malang regency Indonesia - Sri Widowati; Muhammad Ari Arfianto; Rosyidul 'Ibad, Muhammad; Fikri, Zahid; Anzalna Rahma, Alaili (University of Muhammadiyah Malang, 2023)
Introduction: Adolescents with mental health criteria can form a positive self-identity. One of the developments of self-identity can be influenced by parenting factors. Objectives: The purpose of this study was to identify the relationship between democratic, authoritarian, and permissive parenting on the formation of adolescent self-identity in Karangploso District, Malang Regency. Methods: The research design was a cross-sectional study; data were collected using the Parental Authority Questionnaire (PAQ) and the Adolescent Self-Identity Scale. The sample in this study was 80 respondents; the sample selection criteria used a purposive sampling technique and then statistically tested using Spearman rank. This research has obtained ethical approval with the number No.E.5.a/261/KEPK-UMM/XII/2021. Results: The crosstab analysis showed that the most frequently used form of parenting was democratic, with the formation of adolescent self-identity at a moderate level (53.6%). Meanwhile, the bivariate analysis results with Spearman rank showed that the authoritarian, democratic, and permissive parenting styles all had a relationship with adolescent self-identity with a P value of <0.05. Conclusions: The majority of parents apply democratic parenting to form adolescent self-identity; this is because, at this age, adolescents enter a phase of self-discovery with the characteristics of having the ability to think conceptually and want to be appreciated so that the application of this democratic parenting pattern can accommodate the formation of self-identity towards moderate and high.